Dynamic conditional bias-adjusted carry cost rate futures hedge ratios - Dean Leistikow; Yi Tang; Wei Zhang (Journal of Risk and Financial Management, 2022)
This paper proposes new dynamic conditional futures hedge ratios and compares their hedging performances along with those of common benchmark hedge ratios across three broad asset classes. Three of the hedge ratios are based on the upward-biased carry cost rate hedge ratio, where each is augmented in a different bias-mitigating way. The carry cost rate hedge ratio augmented with the dynamic conditional correlation between spot and futures price changes generally: (1) provides the highest hedging effectiveness and (2) has a statistically significantly higher hedging effectiveness than the other hedge ratios across assets, sub-periods, and rolling window sizes.
Keywords: G01; G11; G12; G17; 330; carry cost rate; hedge ratio; conditional hedge ratio; bias adjustments